Bibliometric Analysis of Socio-Political Research on Capital Relocation: Examining Contributions to the Case of Indonesia - Tawakkal Baharuddin; Achmad Nurmandi; Zuly Qodir; Hasse Jubba; M. Syamsurrijal (Journal of Local Government Issues (LOGOS), 2022)
The idea of ​​building a new capital city is a recent issue that has been widely discussed in Indonesia. To help observe the urgency of these ideas, research results are needed by analyzing several published documents available globally. This helps study the evolution of the discourse of moving the new capital city through research results. This study aims to fill the gap in previous research on moving the State Capital with a bibliometric analysis approach. The bibliometric analysis research method maximizes the analytical tool, namely Vosviewer. This approach explores relocating the National Capital by reviewing publications and research globally, especially in the socio-political field indexed in the Scopus database. This study found 176 most relevant publication documents and was considered influential on other published documents. In line with the discourse on relocating the Indonesian capital, this study finds that the tendency of Indonesian researchers to distribute publication documents is very minimal globally, but the results of this study view that the study of the relocation of the National Capital has the potential to be extensively researched in the future, especially in the socio-political field. Some topics are relevant to be studied, including urbanization, regional development, economic development, political geography, government relocation, modernization, identity construction, state-building, climate change, and others. The contribution of this research becomes a reference for further researchers in determining the position of contributions to the development of more relevant research in the future.